Temperature Distribution Performance in LPG Stove-Heated Reactor in Slow Biomass Pyrolysis Process - Putri Mutia Monica; Syamsuddin Yani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Slow pyrolysis is a biomass conversion method commonly used on a laboratory scale. This process takes place in a reactor and uses LPG gas as a heating source. In addition to the pyrolysis reactor design, the reactor configuration and operational conditions affect the amount and characteristics of the final product produced. This pyrolysis process is affected by several operational conditions, namely particle size, heating rate, temperature, and carbonization time. This study aims to observe the temperature distribution in a fixed-bed pyrolysis reactor made of stainless steel using three different types of biomass: rice straw, corn cobs, and peanut shells. Temperature distribution observations were carried out at three vertical points: at the bottom of the reactor (T1), the center of the reactor at a height of 15 cm (T2), and the surface at a height of 30 cm (T3). The results of the study showed that the temperature distribution in a fixed-bed cylindrical pyrolysis reactor with dimensions of 42 cm in diameter, 55 cm in height, without insulation without a stirrer, and made of stainless steel showed an uneven temperature distribution from the point at the bottom of the reactor (T1), in the middle of the reactor (T2) and on the surface of the biomass (T3). The temperature difference at the observation points T1, T2, and T3 occurred in both rice straw, peanut shells, and corn cobs. The uneven temperature distribution in the pyrolysis reactor was caused by several things, including the reactor design not supporting uniform heat distribution, the characteristics of agricultural waste biomass, the absence of biomass stirring, so that the biomass remained still (steady) and heat did not spread homogeneously even though the biomass had been given pre-treatment such as uniform size and reduction of water content through heating. To prevent temperature differences, the addition of a jacket to the reactor design could maintain even heat circulation around the reactor and reduce heat transfer from the reactor directly to the environment.